1999
DOI: 10.1002/(sici)1521-3773(19990802)38:15<2222::aid-anie2222>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin-Based Thin-Film Molecular Materials with Highly Adjustable Nanoscale Porosity and Permeability Characteristics

Abstract: Mesoporous thin films based on neutral, porphyrin-bridged, tetrarhenium "square" compounds (metallacycles) display permeability to molecules smaller than the dimensions of an individual square cavity, but blocking behavior toward larger species (see schematic representation). The characteristic permeant size cutoff can be systematically and predictably manipulated by decorating the walls of the porphyrin square with axially bound, mono-, bi-, and tetradentate ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0
2

Year Published

2001
2001
2006
2006

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 1 publication
5
73
0
2
Order By: Relevance
“…While 2 allowed permeation of iron phenanthroline, thin-film membranes of the functionalized square 3 blocked its permeation, allowing only trace amounts through even after 250 h of exposure. However, 3 remained highly permeable to phenol; similar findings have been reported based on electrochemical measurements [14,15]. This is a strong indication that transport through the porphyrin square films is governed by diffusion of penetrants through the interior square cavities rather than through voids between the squares.…”
Section: Introductionsupporting
confidence: 84%
“…While 2 allowed permeation of iron phenanthroline, thin-film membranes of the functionalized square 3 blocked its permeation, allowing only trace amounts through even after 250 h of exposure. However, 3 remained highly permeable to phenol; similar findings have been reported based on electrochemical measurements [14,15]. This is a strong indication that transport through the porphyrin square films is governed by diffusion of penetrants through the interior square cavities rather than through voids between the squares.…”
Section: Introductionsupporting
confidence: 84%
“…Clearly, in the limit where L approaches zero, the approximation of the effective generator area by the tip area becomes exact. For the approach conditions used here, we have previously found that the approximation works well; the simplified SECM analysis returns transport parameters that agree closely with those obtained from exact analyses of RDE (17,21) and microelectrode measurements. Given the approximate equivalence under these conditions, we have replaced the difficult footprint͞ collection-efficiency problem with the simpler problem here of calculating the film flux as if the film were located at the tip electrode.…”
Section: ϫ1/2supporting
confidence: 70%
“…Consistent with channel formation, molecular-square film samples that retain some crystallinity typically transport probe molecules 20 to 50 times faster than amorphous metallopolymeric materials displaying similar molecular size cutoffs (18,19). Finally, with large squares, cavity functionalization has been demonstrated (20), and the functionalization chemistry has been exploited to tune molecular size cutoffs in a systematic fashion (13,17,21).…”
mentioning
confidence: 91%
“…56,58 In their studies, advantage was taken of zinc ions configured in the center of each porphyrin wall to axially ligate difunctional or tetrafunctional porphyrins and predictably reduce the cavity dimensions (Figure 7). Benkstein and Williams extended the investigations to thin films composed of the molecular rectangle, 10.…”
Section: Applications: Molecular Sievingmentioning
confidence: 99%